Fiscal Policy Sustainability in Nigeria: ARDL Bounds Testing Technique - Adebisi, Dauda Gbolagade; Salako, Gbadebo (Asian Journal of Empirical Research, 2020)
This study investigates fiscal policy’s sustainability in Nigeria from 1961-2016, using annual data of public revenues and expenditure, all as a ratio of GDP. The study applies ARDL bounds testing cointegration technique to determine an equilibrium relationship between the variables. Also, Autoregressive Distributed Lag (ARDL) technique of data analysis is employed to examine the compliance of the government of Nigeria with the budget constraint equation. The results show no equilibrium occurs between public revenue and expenditure, indicating absence of sustainability in the government finances in Nigeria. It is expedient, therefore, that government expands the tax base, reduce tax rates and be cautious in her spending to avoid unproductive expenditure.